Sejarah Perkembangan Al-Qur'an Braille di Indonesia - Ahmad Jaeni (Lajnah Pentashihan Mushaf Al-Qur'an, 2015)
This paper presents historical development of the Quranic Braille in Indonesia which is so dynamic. Based on the analysis of various sources of historical documents, the history of the copying of the Quranic Braille in Indonesia went through several phases, namely the Phase of duplication, that of adaptation and that of standardization. The emergence of these phases cannot be separated from the two of the growing streams of writing at the time, each of which was developed by Yaketunis and Wyata .The Phase of standardization becomes the most important phase because all the difference in the copying of the Qur'an in Braille can be managed to be put together, so that it became the basis of the birth of the Decision of the Minister of Religion No. 25 of 1984 on the Determination of the standard of Indonesian Quranic Mushaf, including the Qur'anic Mushaf for Braille standard.